HIV‐1 NNRTIs: structural diversity, pharmacophore similarity, and impliations for drug design. Issue 1 (26th April 2011) - Zhan, Peng; Chen, Xuwang; Li, Dongyue; Fang, Zengjun; De, Erik; Liu, Xinyong
<x xml:space="preserve">Abstract</x> Nonnucleoside reverse transcriptase inhibitors (NNRTIs) nowadays represent very potent and most promising anti‐AIDS agents that specifically target the HIV‐1 reverse transcriptase (RT). However, the effectiveness of NNRTI drugs can be hampered by rapid emergence of drug‐resistant viruses and severe side effects upon long‐term use. Therefore, there is an urgent need to develop novel, highly potent NNRTIs with broad spectrum antiviral activity and improved pharmacokinetic properties, and more efficient strategies that facilitate and shorten the drug discovery process would be extremely beneficial. Fortunately, the structural diversity of NNRTIs provided a wide space for novel lead discovery, and the pharmacophore similarity of NNRTIs gave valuable hints for lead discovery and optimization. More importantly, with the continued efforts in the development of computational tools and increased crystallographic information on RT/NNRTI complexes, structure‐based approaches using a combination of traditional medicinal chemistry, structural biology, and computational chemistry are being used increasingly in the design of NNRTIs. First, this review covers two decades of research and development for various NNRTI families based on their chemical scaffolds, and then describes the structural similarity of NNRTIs. We have attempted to assemble a comprehensive overview of the general approaches in NNRTI lead discovery and optimization reported in the literature during the last decade. The successful applications of medicinal chemistry strategies, crystallography, and computational tools for designing novel NNRTIs are highlighted. Future directions for research are also outlined.